Studies on the Quality Changes of Frozen Fish in Retail Cold Stores - P.T., Lakshmanan; P.R.G., Varma; T.S.G., Iyer (Fishery Technology, 2025)
The changes in the quality of five commercially important fishes, namely, black pomfret (Parastromateus niger), whitepomfret (Pampus argenteus), seer fish (Scomberomorus sp.), mullet (Mugil cephalus) and pearlspot (Etroplus suratensis), quick frozen at -40°C and kept in five selected retail cold stores having average temperatures of -11 .2, -4.43, -10.4, - 11 .25 and -4.55°C and a control stored at -18°C were studied and shelf life evaluated. The keeping quality of the fish was studied by following sensory, biochemical and microbiological changes. The study showed that the above fishes could be kept in good quality upto 10-12 weeks if the temperature is maintained below - 10°C. Fluctuating and high temperature in the cold stores are the limiting factors in the quality of frozen fish from retail outlets.